Pemanfaatan Energi Surya untuk Sistem Refrigerasi Berbasis Siklus Adsorpsi - Ali, Mukhlis (Universitas Nusa Putra, 2020)
Application of solar adsorption refrigeration systems has developed significantly since 1980’s. Although it has some advantages like noiseless, non-corrosive and environment friendly operation (because solar energy is one of green and renewable energy), but until now the application still cannot compete with the traditional vapor compression refrigeration systems. Fortunately, due to the increasing of awareness about ozone depletion and global warming, green technology including solar adsorption refrigeration systems still becomes priority research is developed by some country. Recent research in application of solar adsorption refrigeration systems not only focus in how to increase the coefficient of performance (COP) like the use of various collectors or working pairs but also how to implement the systems so that suitable with the location that it will be applied. Nowadays, application of solar adsorption refrigeration systems mostly varies into 3 categories: ice maker, cool chamber and humanitarian aid. And the application’s usage usually implement in remote area that far from grid electricity.